Mass Spectral Fragmentation Pattern of 2,3-dihydrothieno-[2,3-b] Quinoline-S-Oxide and its Benzo(h)Derivative upon Electron Impact - Rajendran, S.P.; Shanmugam, P. (Asian Journal of Chemistry, 2010)
A mass spectral study of 2,3-dihydrothieno(2,3-b)quinoline-S-oxide and its benzo(h) derivative is reported. In the spectra, the molecular ion, which appears as the base peak fragments by the loss of CH3, O, OH, H2O, CO, CHO, SH, CHS, SO and SOH species. Rearrangement of molecular ion to a cyclic sulphenate sturcture which initiates the loss of CO, CHO, SH and CHS was suggested. A highly abundant peak appears at M-74 and it is accounted.